Evaluation of Reference Services: An Analysis of Reference Services at Turkish Grand National Assembly Library - Çakmak, Tolga; Tırnavalı, Sercan (Information World, 2020)
As one of the conventional services of libraries, reference services are renovated in line with the advancements in technology. The data extracted from these services are used to assess the impact of these services. This study aims to describe user requests in the reference services and responses provided to these requests in the Turkish Grand National Assembly (TGNA) Library based on the data extracted from such services. For this purpose, a form was created to record the requests received by the reference unit. The data set used in the study was obtained by penetrating the requests into this form. The pre-processing phase of the data gathered from 171 transactions in 43 working days was carried out by using KNIME software. Following the preprocessing phase, the data analyzed with SPSS software and findings were presented with descriptive statistics. The findings of the study declared that the users frequently request books from the reference unit, and as an interaction environment e-mail is a very used tool in responding requests and most of the requests were reacted in an hour. At the end of the study, recommendations for potential improvements of the reference services of the TGNA Library were made. As an originality value, this research gives an exemplary approach for decision-makers considering the effectiveness of reference services implemented in libraries.